2017
DOI: 10.2139/ssrn.3076851
|View full text |Cite
|
Sign up to set email alerts
|

Global Cities, Connectivity, and the Location Choice of MNC Regional Headquarters

Abstract: One of the manifestations of the increasing diversity in multinational corporation (MNC) operations is the growing importance of regional headquarters (RHQs). RHQs assume an intermediary, bridging role between the corporate headquarters and local affiliates and other actors in their respective regions. They can have a coordination and control (i.e., administrative) mandate as well as an opportunity seeking (i.e., entrepreneurial) mandate. Since these mandates require RHQs to interact with various internal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(74 citation statements)
references
References 117 publications
(205 reference statements)
3
70
0
1
Order By: Relevance
“…Inner Dublin’s daytime working population only broke through the 500,000 mark in 2016; those employees able to work from home during the pandemic who are not public sector workers are employed to a large degree in advanced service, tech and finance firms (Dublin is in the ‘top 3’ of RHQ‐hosting cities in Europe; Belderbos et al . 2017)), whose presence in Dublin is predicated upon otherwise smooth relational flows (transatlantic, Anglo‐Irish and with major financial centres in Europe and the Gulf) of people, capital and information (Sokol et al . 2008).…”
Section: The Case Of Dublin Irelandmentioning
confidence: 99%
“…Inner Dublin’s daytime working population only broke through the 500,000 mark in 2016; those employees able to work from home during the pandemic who are not public sector workers are employed to a large degree in advanced service, tech and finance firms (Dublin is in the ‘top 3’ of RHQ‐hosting cities in Europe; Belderbos et al . 2017)), whose presence in Dublin is predicated upon otherwise smooth relational flows (transatlantic, Anglo‐Irish and with major financial centres in Europe and the Gulf) of people, capital and information (Sokol et al . 2008).…”
Section: The Case Of Dublin Irelandmentioning
confidence: 99%
“…Relatedly, one could ask where different headquarters activities should be located in order to optimize the cohesion of the overall system while minimizing internal coordination and transaction costs. The paper by Belderbos et al () highlights how principles of organizational transaction costs can be applied to the study of location choices for some elements of the headquarters system (in their case, regional headquarters).…”
Section: Charting the Path Forwardmentioning
confidence: 99%
“…Finally, Belderbos et al () address in their paper entitled ‘ Global Cities, Connectivity, and the Location Choice of MNC Regional Headquarters ’, the choice of location for regional headquarters on the city level. Specifically, the authors investigate whether a regional headquarters location is driven by the characteristics of the city (its connectivity) and by its distance from the corporate headquarters and regional affiliates.…”
Section: Overview Of the Articles Of The Special Issuementioning
confidence: 99%
“…Global cities are special places for MNEs because of the cosmopolitan workforce, advanced producer services, and global interconnectedness, which provides MNEs with potentially lower transaction costs due to their arms‐length nature of transaction in such places (Goerzen, Asmussen, & Nielsen, ; McCann & Mudambi, ; Rossi, Beaverstock, & Taylor, ). Belderbos, Du, and Goerzen () showed subsidiaries located in global cities gain from being located closer to global knowledge pipelines that provide them with easier access to such knowledge assets. Rossi et al () showed that global city location also plays a role in the allocation of value‐chain activities across the MNE, although their study neglects the hinterland location options.…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%